Does corruption promote the emigration of young and skilled labor? Exploring the Philippines' case - Capurcos, John Romer Mangubat (Animo Repository, 2024)
Previous studies investigated the relationship between corruption and migration and found out that corruption may directly or indirectly influence people to leave their country of origin. Curiously, there is a dearth of literature on the evidence of corruption-migration nexus in the Philippine context. Thus, in view of the severe corruption and consistent international labor migration in the Philippines, this descriptive research embarked to fill the scholarship gap by shedding light on the question: “How does corruption influence the decision among young and skilled Filipinos to migrate?”. Accordingly, the research undertook the conduct of nine life story interviews and two focus group discussions involving young and skilled Filipino migrants, with a total of 17 informants. Using Merkle et al.’s Framework on Corruption-Migration Nexus (2017), which posits that corruption may directly or indirectly undermine people’s quality of life and state of human security thereby pushing people to leave a country mired in corruption, this research argues that that there may be a strong direct link between corruption and migration in the Philippines manifested by the informants’ negative feelings brought about by corruption and the ensuing decision to leave the country. The research documents feelings of hopelessness, helplessness, and neglect of young and skilled migrants relative to the status quo (where corruption persists), which may be a novel indicator of such direct nexus found in a specific country context. Indirect nexus of corruption and migration in the Philippine context could have also revealed by this research. The informants' poor economic security, health security, and quality of life have led to aspirations for a better quality of life, which thereby led to their actual migration. The informants reported that said insecurities and the ensuing poor quality of life were perceived to be worsened by corruption. This research argues that corruption and poor quality of government in the Philippines may influence young and skilled Filipinos to emigrate and provides a thick description of how such link transpires considering the lived experiences of young and skilled Filipino migrants. This research also finds that said factors may also be influential in said migrants’ decision to not return to the Philippines. Resulting reflections then delve into how good governance and an impartial government - a government that fights corruption, promotes good quality of life, provides impartial access to public services, and acts towards public interest, may be useful on tackling the flight of human capital and on successfully facilitating their return. Ultimately, the findings are relevant to students of development and public policy, academia members, and the public sector, especially when said sectors investigate further the links between corruption and migration in specific countries or inquire about the value of encouraging the return and retainment of a country’s young and skilled citizens.